2023
DOI: 10.1111/fwb.14140
|View full text |Cite
|
Sign up to set email alerts
|

The role of small‐scale environmental gradients on trematode infection

Abstract: Parasitism rates can vary dramatically across large and small spatial scales. Such heterogeneity in infection is driven by variation in environmental factors that influence the probability of host and parasite encountering each other (encounter filters) and of genetic and physiological factors that alter whether that encounter results in a successful infection (compatibility filters). Here, we investigated how infection in first‐intermediate hosts (snails) by trematode parasites is influenced by small‐scale va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The temperature in Ordos is about 15–27 °C from May to July, and about 25–36 °C from July to September. The lower temperature from May to July compared to July to September is likely to affect the reproduction of some trematodes, and it has been confirmed that temperature affects the growth and reproduction of trematodes ( Larsen and Mouritsen, 2014 ; Poulin, 2006 ; Resetarits and Byers, 2023 ). In addition, the rainfall from July to September is heavy, and the grassland is waterlogged to form a lot of shoal, which is conducive to the reproduction of freshwater snails, resulting in a high positive rate of snail trematodes.…”
Section: Discussmentioning
confidence: 94%
“…The temperature in Ordos is about 15–27 °C from May to July, and about 25–36 °C from July to September. The lower temperature from May to July compared to July to September is likely to affect the reproduction of some trematodes, and it has been confirmed that temperature affects the growth and reproduction of trematodes ( Larsen and Mouritsen, 2014 ; Poulin, 2006 ; Resetarits and Byers, 2023 ). In addition, the rainfall from July to September is heavy, and the grassland is waterlogged to form a lot of shoal, which is conducive to the reproduction of freshwater snails, resulting in a high positive rate of snail trematodes.…”
Section: Discussmentioning
confidence: 94%